1993
DOI: 10.1177/109634809301600205
|View full text |Cite
|
Sign up to set email alerts
|

Job Satisfaction, Job Involvement, Job Security, and Customer Focus of Quick-Service Restaurant Employees

Abstract: This study examined the relationships of customer focus and job satisfaction, job involvement, and job security for quick-service restaurant employees. Results indicated that job satisfaction, job involvement, and job security do tend to predict customer focus for restaurant employees, and, consequently, increasing job satisfaction, job involvement, and job security may improve an employee's customer focus. Having a better understanding of employees and factors which affect their focus on the services they pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
3
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 18 publications
3
25
3
2
Order By: Relevance
“…These results were consistent with main stream research (Mowday et al 1982;Lincoln and Kalleberg 1990;Ross and Reskin 1992;Dienhart and Gregoire 1993;Mueller, Boyer, Price and Iverson 1994;Yousef 1998;Oshagbemi 2000). Lincoln and Kalleberg (1990) in their study of work attitudes in the USA and Japan found that satisfaction was positively and strongly correlated with commitment.…”
Section: Correlation Between Satisfaction and Commitmentsupporting
confidence: 90%
“…These results were consistent with main stream research (Mowday et al 1982;Lincoln and Kalleberg 1990;Ross and Reskin 1992;Dienhart and Gregoire 1993;Mueller, Boyer, Price and Iverson 1994;Yousef 1998;Oshagbemi 2000). Lincoln and Kalleberg (1990) in their study of work attitudes in the USA and Japan found that satisfaction was positively and strongly correlated with commitment.…”
Section: Correlation Between Satisfaction and Commitmentsupporting
confidence: 90%
“…In line with Dienhart and Gregoire, LaLopa [26] argued that job satisfaction is a significant predictor of organizational commitment. Different with Dienhart and Gregoire [13] and LaLopa [25], research which conducted by Markovits et al [33] suggested that affective organizational commitment was found to be most influential with respect to levels of intrinsic and extrinsic job satisfaction. In line with research which conducted by Markovits et al [33], research which conducted by Sharma and Bajpai [50] and Adeloka [1] also suggested that organizational commitment is being proven as the catalyst for enhancing the job satisfaction level of employees.…”
Section: Organizational Commitment and Job Satisfactionmentioning
confidence: 82%
“…The first opinion, job satisfaction is a significant predictor of organizational commitment and the second opinion, organizational commitment is a significant predictor of job satisfaction. Dienhart and Gregoire [13] and LaLopa [26] were some of the researchers that supported the first opinion. Dienhart and Gregoire [13] revealed that many studies use different facets of satisfaction to predict employee attributes such as performance, organizational commitment, and service quality.…”
Section: Organizational Commitment and Job Satisfactionmentioning
confidence: 92%
See 1 more Smart Citation
“…Desphande et al (1993) found out that customer orientation is related positively to business performance. Existing researches, such as Babakus et al (2009), Dienhart and Gregoire (1993), Donavan, Brown, and Mowen (2004), and Kusluvan (2003), have discovered that customer orientated employees are more successful in job performance exhibiting a higher organizational citizenship behavior (Ro & Chen, 2011). Saxe and Weitz (1982) have developed a SOCO scale to measure sales/customer orientation within an organization's sales staff.…”
Section: Customer Orientationmentioning
confidence: 99%